Macropinocytic entry of isolated mitochondria in epidermal growth factor-activated human osteosarcoma cells. Issue 1 (December 2017) - Patel, Dipali; Rorbach, Joanna; Downes, Kate; Szukszto, Maciej; Pekalski, Marcin; Minczuk, Michal
Abstract Mammalian mitochondria can be transferred between cells both in culture andin vivo . There is evidence that isolated mitochondria enter cells by endocytosis, but the mechanism has not been fully characterised. We investigated the entry mechanism of isolated mitochondria into human osteosarcoma (HOS) cells. Initially we confirmed that respiratory-competent cells can be produced following incubation of HOS cells lacking mitochondrial DNA (mtDNA) with functional exogenous mitochondria and selection in a restrictive medium. Treatment of HOS cells with inhibitors of different endocytic pathways suggest that uptake of EGFP-labelled mitochondria occurs via an actin-dependent endocytic pathway which is consistent with macropinocytosis. We later utilised time-lapse microscopy to show that internalised mitochondria were found in large, motile cellular vesicles. Finally, we used confocal imaging to show that EGFP-labelled mitochondria colocalise with a macropinocytic cargo molecule during internalisation, HOS cells produce membrane ruffles interacting with external mitochondria during uptake and EGFP-labelled mitochondria are found within early macropinosomes inside cells. In conclusion our results are consistent with isolated mitochondria being internalised by macropinocytosis in HOS cells.